Extracorporeal Membrane Oxygenation Support for Cardiac Dysfunction Due to Kawasaki Disease Shock Syndrome - Zhang, Han; Xie, Lijian; Xiao, Tingting (Frontiers in Pediatrics, 2019)
Kawasaki disease (KD) is an acute, inflammatory vasculitis in children of early childhood, which is predominantly involving medium-sized arteries, and treated with intravenous -globulin (IVIG) and oral aspirin. KD with hemodynamic instability, characterized by either systolic blood pressure ⩾ 20% below normal or low perfusion, has been defined as Kawasaki disease shock syndrome (KDSS). The reported incidence of KDSS among patients with KD ranges from 1.9 to 7.0%. Children with KDSS require hemodynamic support and intensive medical care. The pathogenesis of KDSS is not well known, and the diagnosis can be easily missed, leading to mistreatment, which could cause KDSS to become fatal in some cases. Life-threatening cardiogenic shock can occur during the acute phase of KDSS, while the mechanism of cardiac dysfunction due to KDSS is still controversial, and such cases were rarely reported. Here we present the successful use of veno-arterial (VA) extracorporeal membrane oxygenation (ECMO) for cardiac support of a child with KDSS. By doing so, it will be a reminder that KDSS can cause severe cardiac dysfunction, and we should stay vigilant at early stage of the disease.